ISSUES OF DEVELOPMENT OF SOCIAL INFRASTRUCTURE IN RURAL AREAS - To'rayev Abduvohid Qo'ldoshevich; Rafiqjonov Damir Raxim o’g’li (TADQIQOTLAR, 2025)
Abstract: In this article, we will examine the development of social infrastructure in rural areas, its impact on living standards, and its role in the sustainable development of regions. We will examine the state of education, healthcare, transportation, communications, drinking water supply, cultural and sports facilities in rural areas, as well as priority areas for their modernization.